Green Warehousing Practices in the Philippines - Castillo, Romer; Gonzales, Kristhel Ann; Rosales, Danica; Zaraspe, Mary Jane (Indonesian Green Technology Journal, 2022)
Green practice is a worldwide policy and everybody is concerned with sustainable development. This study assessed the green warehousing (GWH) practices in the Philippines and its sustainability dimensions. It utilized a quantitative descriptive-survey approach with questionnaire for data collection. The sample consists of 48 warehouses with warehouse managers as respondents. Statistical tests used were frequency and percentage, mean and standard deviation, Kruskal-Wallis H-Test, and Mann-Whitney U-Test. Results showed most of participating warehouses are located in Parañaque, corporate-owned, small enterprises, operating for 15 years or less, with less than 100 employees, and private. Results further revealed that GWH practices on inventory management and operations were almost always practiced while those on facility design, layout, mechanical handling equipment, staff, and warehouse management system (WMS) were often practiced. Environment, social, and economic GWH practices are also often practiced. Top GWH practices are mostly economic and some social while bottom GWH practices are mostly environmental. Significant differences on GWH practices were found on inventory management, staff, WMS, and social dimension when grouped to location; on WMS when grouped to operation years; and on facility design, environment, and social dimension when grouped to nature of service.  These findings may guide warehouse managers in enhancing their GWH practices as they gear towards attaining sustainability in support to the United Nation’s Sustainable Development Goals. Keywords: green practices; sustainable development; sustainable warehousing; warehouse management